Pengaruh kualitas produk dan promosi terhadap minat beli konsumen di Cafe Dicendana Tigaraksa Kabupaten Tangerang - Oktaviano, Vicky; Riyanto, Slamet; Sutomo (Universitas Tangerang Raya, 2024)
The results of this research show that partially Product Quality obtained a value of 3.111 and Promotion of 2.172, where the value was higher than the table value of 1.993 and the sign score was less than 0.05. Which means that the Product Quality and Promotion variables each have an influence on the Purchase Interest variable. The results of the research simultaneously obtained the following values: fcount of 13.337 where the result was higher than 3.12. Which means that the Product Quality and promotion variables together influence the Purchase Interest variable.